Vandetanib plus gemcitabine versus placebo plus gemcitabine in locally advanced or metastatic pancreatic carcinoma (ViP): a prospective, randomised, double-blind, multicentre phase 2 trial - Middleton, Gary; Palmer, Daniel H.; Greenhalf, William; Ghaneh, Paula; Jackson, Richard; Cox, Trevor; Evans, Anthony; Shaw, Victoria E.; Wadsley, Jonathan; Valle, Juan W.; Propper, David; Wasan, Harpreet; et al. (Elsevier, 2017)
Methods: The Vandetanib in Pancreatic Cancer (ViP) trial was a phase 2 double-blind, multicentre, randomised placebo-controlled trial in previously untreated adult patients (aged ≥18 years) diagnosed with locally advanced or metastatic carcinoma of the pancreas confirmed by cytology or histology. Patients had to have an Eastern Cooperative Oncology Group (ECOG) score of 0–2 and a documented life expectancy of at least 3 months. Patients were randomly assigned 1:1 to receive vandetanib plus gemcitabine (vandetanib group) or placebo plus gemcitabine (placebo group) according to pre-generated sequences produced on the principle of randomly permuted blocks with variable block sizes of two and four. Patients were stratified at randomisation by disease stage and ECOG performance status. All patients received gemcitabine 1000 mg/m² as a 30-min intravenous infusion, weekly, for 7 weeks followed by a 1-week break, followed by a cycle of 3 weeks of treatment with a 1-week break, until disease progression, and either oral vandetanib 300 mg per day once daily or matching placebo. Patients and investigators were masked to treatment assignment. The primary outcome measure was overall survival (defined as the difference in time between randomisation and death from any cause or the censor date) in the intention-to-treat population. This trial has been completed and the final results are reported. The study is registered at EudraCT, number 2007-004299-38, and ISRCTN, number ISRCTN96397434.